Tuturan Penyerta pada Tindak Tutur Meminta dalam Bahasa Korea - Ayu Merlita Sari (JLA (Jurnal Lingua Applicata), 2018)
This research aims to explain the nature of request speech acts in Korean culture and the factors underlying the use of request speech acts. The research data in this study came from non verbal data showed on short message service Kakao Talk. The data were then analyzed using qualitative methods and presented descriptively. By using Pragmatic theory and theory of request strategy by Byeon, it can be concluded that the supportive moves or modified utterances are found to appear before or after the head of the request. There are usages of, 1) opening, 2) preparatory statements, 3) apology, 4) gratitude, 5) rewards, and 6) burden minimizer. The supportive moves indicates the speaker's attempt to soften the speech acts as well as to prevent the request from being rejected. In addition, in the use of supportive moves, Korean speakers also pay attention to the listeners, age, familiarity, speech situation, and social status. This is because the request speech act is a potential threat to the listeners’ face, so that Korean speakers are especially thoughtful in their face-to-face conversation with other people. This behavior is in accordance with the culture of the Korean people who are concerned with the relationship between individuals, which is manifested through the use of supportive moves.